Azacitidine-induced hyperglycaemia. Issue 11 (1st December 2019) - Morton, Adam
Abstract : A case illustrating significant hyperglycaemia with azacitidine therapy for myelodysplastic syndrome is presented. The significance of treatment-induced hyperglycaemia with regard to increased risk of infection, and possible mechanisms of azacitidine-induced hyperglycaemia are discussed.